Dissipative disorder analysis of Homann flow of Walters B fluid with the applications of solar thermal energy absorption aspects - Latif Ahmad; Assmaa Abd-Elmonem; Saleem Javed; Muhammad Yasir; Umair Khan; Yalcin Yilmaz; Aisha M. Alqahtani (Applied Water Science)
Abstract Encountering of entropy generation is meaningful while investigating the energy loss during the operational mechanical system. In particular, the flow of fluid experiencing friction drag and due to which a significant amount of heat transfer occurred. Thus, the thermodynamic system energy conversion is one of the measures of the lost available work and is known as irreversibility. Avoiding of such energy loss can be minimized by introducing the concept of hybridization during the liquid dynamics. This work is initiated to formally characterize and address the significance of irreversible process during the typical Homann flow of viscoelastic liquid. The flow with heat and mass balance aspects are further characterize with the inclusion of thermophoretic and Brownian motion factors. The flow configuration is interpreted in terms of gravitationally affected vertical cylindrical disk, for a better understanding of the impact of irreversible processes, more physical effects in terms of heating source/sink, chemical reaction and solar thermal radiation. New physical impacts are described numerically in terms of flow speed temperatures, nanoparticle volume fraction, displacement thicknesses and entropy generation. Perturbation method is utilized for the reduction of the fourth-order mathematical equation for reducing the problem in to well-posed from ill-posed status. The numerical analysis is carried out by applying one of the built-in commands while using MATLAB software. The buoyancy force factor enhanced the liquid speed, and the concentration of the liquid was determined with uplifted conduct for higher values of chemical reaction parameters. The overall entropy rate is reduced as the Brinkman number and magnetic parameter are increased. The heat transfer flow is increased by internal heat generation. Higher Prandtl and Schmidt numbers significantly affected the isotherms and volume fraction contours.